The angles need to be congruent for the two triangles to be similar.
Hope this helps :)
Answer:
Ok:
Step-by-step explanation:
So f°g . means f(g(x)). (The ° should be more center and bigger but I don't know to do that on a keyboard). f(g(x)) means that you replace the x in f(x) with the g(x) function. i.e:
if f(x) = 2x+2
and g(x) =
f(g(x)) = .
Similarly, in this case, we get f(x) = 2x-3 and g(x) = 3x-2.
Then, f(g(x)) or f°g(x) is 2(3x-2) - 3.
And we plug in -2 to solve:
2(3(-2)-2)-3.
and get -19.
Check if I am wrong because everyone makes mistakes but that is the way to solve this.
Answer:
12 and 1/4
Step-by-step explanation:
Answer: None of the above
Step-by-step explanation: Because none of them will equal the solution which is 0.5,
1.7 + (-1.2) = 0.5